Em memória da cativa, uma memória que cativa? Análise da construção dos monumentos, da memória e da patrimonialização do Chafariz da Mãe Preta e da Praça da Mãe de Passo Fundo - Baccin, Diego José (2014)
This work has examined the process of patrimonialization of two cultural historical heritage assets in Passo Fundo. The fountain of Mãe Preta 1863 (before the end of slavery in Brazil), which referes to enslaved Mãe Preta. And the creation of a monument to Mãe Preta a century after the first, in 1964. The problematic intends to identify the possible relation problems between the subjects, which took place at the creation point of both monuments. In order to determine how the composition process of these memory sites as elements of historic matter occurred, turning these assets, which carry elements of materiality history - the monuments themselves, into historic symbols, as well as, of symbolic immateriality since the studied assets present characteristics which report to compensatory concepts, and are assigned different and contradictory meanings and representations. The study aims to understand the relations which were established under local political life and which led to the creation of these refered monuments; understanding the cultural, social and symbolic relations; pondering the various significations and representations processed in the course of history, and the uses to which they were refered to, in terms of construction and reconstruction of meaning based on the relationship between history and memory, or memory and history, to consider the existence, not of a causal link between the fountain and the monument. The theoretical foundation is supported by two perspectives: one by Jacques Le Goff´s considerations stating that memory is the property of retaining certain information. The other by Roger Chartier which says that past history reality reaches historians only through representations, which at different times form social reality giving present its meaning. Enabling the access to the available information about the assets, the research was based on iconographic record analysis, seeking to understand how the monuments were represented as objects and how, as the objects were created, the individuals represented the monuments. Written records were consulted with the intention of reconstructing the information found in them in order to recognize the convergent and divergent points about historical data involving the target Fountain and Monument. The interview process was held using oral history. And finally, the information-gathering form was used, and based on the collected data provided, we have learned how the monuments are currently understood, represented, and which historic facts remain as community memory. The instrument of analysis used in this study was produced by sampling. Thus, what currently remains about the memory of these monuments is concerned with their history, although it may seem different, history makes new readings and interpretations possible, in many cases what might be evident is an erasure memory process, being meaningless to collective history, which favors social or political oblivion